Feasibility of using the Residential Environment Impact Scale (REIS) and the Assessment for Occupation and Social Engagement (ATOSE) as assessment tools within Engo Residential Aged Care Facilities in the Free State province, South Africa - Kilian, Melissa (University of the Free State, 2020)
Introduction: The occupational wellbeing of elders is influenced by the physical and social long-term care environments in which they live. Elders living in Residential Aged Care Facilities are often exposed to occupational injustices and become institutionalised as a result of an environment that does not provide adequate occupational opportunities, support and stimulation. Purpose: The main purpose of this study was to investigate the feasibility of two occupation-based assessment tools, the REIS and ATOSE within Residential Aged Care Facilities affiliated with the Engo organisation. The REIS and ATOSE have not previously been used within the South African aged care sector or the Engo organisation. Methods: An embedded mixed methods approach with a qualitative focus was employed. The research was conducted in two phases. The first phase saw the researcher administering the two assessment tools within three participating facilities and providing each participating facility with their report containing the REIS and ATOSE findings. The reports contained quantitative statistics as yielded by each assessment, supported with descriptive information yielded by qualitative notes made by the researcher during the assessment period of phase one. During the second phase a discussion group employing the nominal group technique, was held with leadership staff of the participating facilities. Leadership staff considered and deliberated on the findings presented in the reports in order to identify possible enablers and obstacles of using the REIS and ATOSE assessment tools. A thematic analysis was employed during data analysis. Findings: The findings were categorised into two main themes, i.e. organisational culture and occupational justice issues. The findings of the REIS and ATOSE assessments (phase 1) and the nominal discussion group (phase 2) indicated an organisational culture which is dominated by a top-down management approach and distinguished by a medicallydominated care approach. Leadership staff struggled to directly conclude what enablers and barriers exist for using the REIS and ATOSE assessments. The findings of the research process, however, indicate that the assessments yield practical and usable information but the current Engo organisational culture is not receptive to implement the findings. Conclusions: The main contribution of this study is the exploration of two previously unused occupation-specific tools in the South African aged care sector, which presented information about elder communities that occupational therapists should consider when practicing in these environments to effect person-centred culture change.
Dissertation (M.Occ. (Occupational Therapy)--University of the Free State, 2020
Keywords: Residential Environment Impact Scale (REIS); Assessment Tool for Occupation and Social Engagement (ATOSE); Residential Aged Care Facilities; Organisational culture; Occupational justice; Wellbeing; Quality of life; Occupational therapy assessment tools; Person-centred care